Institutionalising diasporic Islam: multiculturalism, secularism and the integration of Muslim immigrants in Britain - Wardana, Amika (Indonesian Journal of Islam and Muslim Societies, 2013)
The integration of Muslim immigrants in Western countries especially Britain hasattracted wider attention both from academia, policymakers and public in gen-eral. Their different religion (i.e. Islam) has been regarded as the crucial factorsin the process contextualised by the socio-political circumstances of the hostsociety and the existence transnational link to the home country encouragingthem to reproduce and transplant their ethno-religious tradition in diaspora. Thearticle addresses the interplay between, on the one hand, the strong and weak-ness of the politics of multiculturalism and the secularisation and desecularisationof British society, and on the other, the institutionalisation of Islam in Britain amidstthe persistent internal divisions and fragmentations of minority Muslim immi-grant communities. As the result, Muslim immigrants have set up an ethno-reli-gious integration trajectory through their own established socio-religious institu-tions and associations in parallel with the host country social and political ones.Integrasi  imigran  Muslim  di  negara-negara  Barat  khususnya  Inggris  telahmemeroleh perhatian luas baik dari kalangan akademisi, pembuat kebijakan dan publik pada umumnya. Keragaman agama mereka (termasuk Islam) dipandangsebagai faktor penting dalam proses yang dikontekstualisasi oleh lingkungan sosio-politik masyarakat setempat dan hubungan transnasional yang ada dengan negaraasal yang mendorong mereka mereproduksi dan mentransplantasi tradisi etno-religi mereka di diaspora. Artikel ini memaparkan hubungan saling pengaruhantara  kekuatan  dan  kelemahan  politik  multikulturalisme  di  satu  sisi,  daninstitusionalisasi Islam di Inggris yang melahirkan pembagian dan fragmentasiinternal di kalangan komunitas imigran Muslim minoritas di sisi lain. Akibatnya,imigran Muslim telah membangun peta integrasi etno-religi melalui lembaga-lembaga dan asosiasi-asosiasi sosio-religi mereka yang sudah mapan paraleldengan lembaga dan asosiasi social dan politik negara setempat.